2018
DOI: 10.3390/min8120589
|View full text |Cite
|
Sign up to set email alerts
|

Mycoextraction: Rapid Cadmium Removal by Macrofungi-Based Technology from Alkaline Soil

Abstract: Fungi are promising materials for soil metal bioextraction and thus biomining. Here, a macrofungi-based system was designed for rapid cadmium (Cd) removal from alkaline soil. The system realized directed and rapid fruiting body development for subsequent biomass harvest. The Cd removal efficiency of the system was tested through a pot culture experiment. It was found that aging of the added Cd occurred rapidly in the alkaline soil upon application. During mushroom growth, the soil solution remained considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
5
0
2
Order By: Relevance
“…DEGs associated with cell wall remodeling may play a role in covalent Cd binding as found in this study and elsewhere ( 5 , 58 , 63 , 64 ), probably through the modification of cell wall chemistry. Besides cell wall protection, transmembrane Cd importers were found actively involved in Cd stress response.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…DEGs associated with cell wall remodeling may play a role in covalent Cd binding as found in this study and elsewhere ( 5 , 58 , 63 , 64 ), probably through the modification of cell wall chemistry. Besides cell wall protection, transmembrane Cd importers were found actively involved in Cd stress response.…”
Section: Discussionsupporting
confidence: 79%
“…A transcriptomic analysis of tall fescue ( Festuca arundinacea ) showed that several metal transporters, GSH, and transcriptional factors were simultaneously induced by Cd ( 50 ). In our recent study, we also found that ROS response, cell wall remodeling, metal transport, and Cys synthesis were involved in the Cd stress response in P. ostreatus ( 5 ), and glycolysis/gluconeogenesis, pentose phosphate pathway and glycine metabolism were substantially induced by Cd treatment in Purpureocillium lilacinum strain YZ1 ( 51 ). With the information above, it is possible to establish an overview of global cellular responses to Cd stress systematically.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations